A 52-week multicenter retrospective real-world study on effectiveness and safety of dupilumab in children with atopic dermatitis aged from 6 to 11 years - Cataldo Patruno; Gabriella Fabbrocini; Giuseppe Lauletta; Valeria Boccaletti; Cristiana Colonna; Riccardo Cavalli; Iria Neri; Michela Ortoncelli; Donatella Schena; Luca Stingeni; Katharina Hansel; Vincenzo Piccolo; et al. (Journal of Dermatological Treatment, 2023)
Background: Dupilumab has been shown to be a safe and effective drug for the treatment of atopic dermatitis (AD) in children from 6 months to 11 years in randomized clinical trials. Aim: The aim of this real-life study was to determine the effectiveness in disease control and safety of dupilumab at W52 in moderate-to-severe AD children aged 6-11 years. Methods: All data were collected from 36 Italian dermatological or paediatric referral centres. Dupilumab was administered at label dosage with an induction dose of 300 mg on day 1 (D1), followed by 300 mg on D15 and 300 mg every 4 weeks (Q4W). Treatment effect was determined as overall disease severity, using EASI, P-NRS, S-NRS and c-DLQI at baseline, W16, W24, and W52. Ninety-six AD children diagnosed with moderate-to-severe AD and treated with dupilumab were enrolled. Results: Ninety-one (94.8%) patients completed the 52-week treatment period and were included in the study. A significant improvement in EASI score, P-NRS, S-NRS and c-DLQI was observed from baseline to weeks 16, 24 and 52. Conclusions: Our real-life data seem to confirm dupilumab effectiveness and safety in paediatric patients. Moreover, our experience highlighted that patients achieving clinical improvement at W16 preserved this condition over time.